Oral Probiotics and Their Impact on Oral Health: Narrative Review - Jasim Witwit , Luma; Malek Hasan , Dhuha (Hammurabi Journal of Medical Sciences, 2025)
On the way to define the scientific literature on the practices then tender of probiotics. Probiotics are living germs existing in the oral cavity; gut by way of intestine and these are engaged by way of nutrition besides oral complements. There have been issued revisions recording on the inhibitor properties of probiotic microbes on the salivary heights of bacterial pathogens. However, there have not been but rare studies on the scientific profits of oral probiotic remedy. According to the research publications, strains including Lactobaccillus and Bifidobacterium shown beneficial effects in reducing bacterial plaque, including S. mutans, in various populations across both short- and long-term periods. Numerous readings have been showed concerning the practice of probiotics in dentistry. To find out more specifically which species support oral health, research using multiple bacterial species and delivery systems is required. Probiotics treat a variety of oral conditions, including periodontal diseases, dental cavities, and halitosis. The market today offers a wide variety of oral probiotic products, and both the more recent and similar items are in high demand. Understanding the impact of oral probiotics on oral fitness, hazard influences, protection, practice, incidence, and potential future uses is made easier by the oral probiotic study.